Scientific Knowledge about Poultry Broiler Farming in Barabanki District of Uttar Pradesh - Jitendra Pratap , M. P. Sagar , Mahesh Chander , N. K. Khyalia and A. K. Chaturvedani (Indian Journal of Extension Education, 2016)
The present investigation was carried out to study the scientific knowledge about broiler farming among poultry farmersin Barabanki district of Uttar Pradesh. The fifteen poultry farmers were selected randomly from each block, making a totalsample size of 75. The study revealed that all the small poultry farmers had medium level of scientific knowledge aboutfeed and feeding management practices, housing management practices and brooding management practices (inoverwhelming majority), while all the large poultry farmers had high level of scientific knowledge about housingmanagement practices, breed selection and identification of quality chicks, feed and feeding management practices andpoultry insurance. All the medium poultry farmers were found to have medium level of scientific knowledge about biosecurity and disease control practices, finance, marketing and poultry insurance, while overwhelming majority of them(93.75%) were having high level of knowledge about feed and feeding management practices. Further, comparison ofknowledge level about scientific broiler farming among the different categories of poultry farmers using one way ANOVAwas also done and the results show that small, medium and large poultry farmers were found to differ significantly at 1%level of significance (p